An Analysis of Digital Resource Implementation on Students’ Speaking Performance - Husnah, Ummu Aina Nafidzatul; Antoni, Nur; Waloyo, Edy (IJET (Indonesian Journal of English Teaching), 2024)
The research entitled “An Analysis of Digital Resources Implementation on Speaking Performance at Vocational High School” is aimed to answer the question how is the implementation digital resources in speaking performance, The research also tries to find out how is the implementation digital resources in speaking performance. In addition, how are the perception of the English teachers and students’ about the implementation of digital resources for speaking performance? The case study as its research method and descriptive qualitative is used as a design of this research. There are three instruments used to collect the data. First is the observation of field-notes, second is the interview for the English teacher and students, and third is a documentation of related lesson plan and syllabus. Techniques for analyzing qualitative data, such as collecting data, reduction data, display data, and conclusion/verification. As a result, it was found that the implementation of digital resource on students’ speaking performance worked well. This was evident from the answers of the students when this method was introduced, because they positively evaluated the method used; they actively participate in the learning process. The implementation of digital resources also greatly supports learning activities to improve this aspect of speaking skills and increase student autonomy, which in turn can facilitate students' the ability to use these skills communicatively.